Epigenetic Effect of Chronic Stress on Dopamine Signaling and Depression. (January 2013) - Moriam, Sofia; Sobhani, Mahbub E.
Because of the complex causal factors leading to depression, epigenetics is of considerable interest for the understanding effect of stress in depression. Dopamine is a key neurotransmitter important in many physiological functions, including motor control, mood, and the reward pathway. These factors lead many drugs to target Dopamine receptors in treating depressive disorders. In this review, we try to portray how chronic stress as an epigenetic factor changes the gene regulation pattern by interrupting Dopamine signaling mechanism.